Hate Crime in Northern Ireland: The Need for Legislation and a Bespoke Version of the Prevent Strategy - Lowe, David (Terrorism and political violence, 2025)
Following the rise in hate crime in Northern Ireland, in 2019 the Northern Ireland Assembly appointed Judge Marrinan to conduct a review into hate crime. Publishing his findings in his review in December 2020, this article examines the key recommendations that should be included in a Hate Crime Bill. As the Assembly is currently suspended, the article examines the hate crime statistics recorded following the publication of the review to illustrate why it is imperative that when it reconvenes, the Assembly introduce a Hate Crime Bill at the earliest opportunity. The article also argues that a prevention programme is introduced alongside the Bill to safeguard and prevent young people being drawn towards paramilitary activity along with hate crime and non-paramilitary terrorist activity. Young people are the focus of introducing an initial programme with the demographics in the hate crime statistics revealing a high number of offenders are that category. Following an examination of current programmes in place and the threat posed by paramilitaries and extremists, including the far right and extreme far right (neo-Nazis), the article recommends the current WRAP programme is developed to help and safeguard young people drawn to the paramilitaries to include hate crime and extremist related terrorism.